A reappraisal of the strength-duration test to assess neuromuscular impairment of critically ill patients. (August 2021) - Fagoni, Nazzareno; Ferretti, Guido; Piva, Simone; Barbieri, Silvia; Rasulo, Frank; Latronico, Nicola; Gobbo, Massimiliano
Abstract: Introduction: Neuromuscular impairment (NMI) affects almost half of critically ill patients. The purpose was to investigate the role of neuromuscular electrical stimulation (NMES) to gain more insight into the nature of the NMI associated with ICU admission. To this aim, we analyzed the strength-duration (S-D) curves of the rectus femoris muscles of ICU patients compared to healthy volunteers. Methods: S-D curves were recorded from 44 healthy volunteers and 29 ICU patients. Three electrophysiological parameters were used to classify the neuromuscular function, from grade 0 (normal function), to grade 3 (no evocable muscle contraction). ICU patients underwent electroneurographic peroneal nerve testing (PENT) to analyze NMI by electroneurography (ENG). Results: Three patients were classified as Grade 0; nine as mild NMI (Grade 1), 13 as Grade 2, and four showed unexcitable muscles (Grade 3). Mean CMAP amplitudes were 6.1, 3.4, 2.9 and 0.81 mV from Grade 0 to Grade 3, respectively. CMAP was inversely correlated to NMI grade (−1.7 mV, R 2 = 0.946, p < 0.05). Conclusions: The normative parameters of the S-D curves obtained by NMES in healthy volunteers allowed identification of NMI in ICU patients. NMES was an affordable tool to evaluate NMI in ICU patients, providing additional information to that obtained by ENG.